Cantang Group (Epinephelus Fuscoguttatus >< Epinephelus Lanceolatus) Hatcheries At The Blitok Installation Of Breach Water Cultivation Fisheries Center (BPBAP) Situbondo, East Java - Adi, Catur Pramono; Aripudin, Aripudin; Prabowo, Guntur; Eny Kristiany, Maria Gorety; Luthfiadi, Nabila Azzahra (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2023)
To achieve success in the maintenance of cantang grouper requires mastery of techniques in good hatchery of cantang grouper (Epinephelus fuscoguttatus >< Epinephelus lanceolatus) in order to produce optimal productivity both in terms of quantity and quality. The aims of this study were: 1) To find out the development and growth rates in cantang grouper hatcheries (Epinephelus fuscoguttatus – lanceolatus), 2) To determine the condition of water quality in cantang grouper hatcheries (Epinephelus fuscoguttaus – lanceolatus), and 3) To determine the feasibility of cantang grouper hatcheries (Epinephelus fuscoguttaus – lanceolatus). The data analyzed in this study include data on growth, water quality, and business analysis. The results of the analysis showed that: 1) In a day the average length increase reached 0.074 cm and the percentage rate of increase in length of cantang grouper larvae for 29 days from the age of D30 – D58 was 7.4%. At the beginning of measuring the length of cantang grouper larvae, the average length was 1.12 cm and at the end of the observation the average value was 3.28 cm. 2) From the results of water quality maintenance, the temperature ranged from 29 – 31°C, oxygen dissolved 4.37 – 4.87 mg/L., pH 7.4 – 7.9, and salinity 28 – 30 ppt, 3) In terms of financial or business feasibility the cantang grouper hatchery activity at the Blitok BPBAP Situbondo Installation can be said to be feasible to do and profitable with a net profit of Rp. 665,904,233/year with an R/C ratio of 3.7. Break Event Point (BEP) price of Rp. 111,539,155/year with production BEP reaching 37,179 heads. Payback Period (PP) for 1 year.